Faktor yang Menentukan Perilaku Konsumen dalam Membeli Produk Beras Kepala di Pasar Tradisional Pasca Pandemi Covid-19 di Kecamatan Barangka Kabupaten Muna Barat - Marsal, La Ode Muhamad Yusuf; Bahari, Bahari; Surni, Surni (Innovative: Journal Of Social Science Research, 2024)
The demand of the community as consumers in Barangka District, West Muna Regency for rice is quite high. This is what causes the demand for rice to tend to increase every year. The purpose of this study is to find out the factors that determine consumer behavior in buying rice in the traditional market after the Covid-19 pandemic in Barangka District, West Muna Regency. The sample in this study is 50 consumers who regularly shop for head rice at traditional markets. The variables in this study include Variables of Consumer Behavior Buying Head Rice (Y), Motivation (X1), Education (X2), Income (X3), Number of dependents (X4), Rice Purchase Value (X5), and Total Rice Purchase (X6). The results of this study show that motivation, rice purchase value and total rice purchase are factors that determine consumer behavior to buy kepala rice products in the traditional market. The value of rice purchases and the total purchase of rice. The value of rice purchases and total rice purchases are the strongest determinants in head rice purchasing behavior.